BLOGI FAN FICTION JAKO NOWY ELEMENT WSPÓŁCZESNEJ KULTURY (REKONESANS BADAWCZY) - Półtorak, Mateusz (In Gremium. Studies in History, Culture and Politics, 2017)
This article is a supplement to a broader discussion about the functioning of the literary Internet users in the new medium. It is also a continuation of the author’s study on the importance of literature in Internet communications. Today, the Internet is not only a source of information, but also the space of social activity in all areas, including culture. This article is an attempt to answer, how does it affect the activity of network users on the modern culture, showing the transformation of the culture and the Internet as a result of the interaction of these two spaces. Analysis of blogs with literary works of internet users, facilitate discussion. Blog gives the the opportunity to study the relation of the sender and recipient and their impact on culture, which will be the main objective of further consideration.